The Hostile Media Phenomenon: Testing the Effect of News Framing on Perceptions of Media Bias. Issue 1 (1st January 2019) - Kim, Kenneth
Abstract : Recent theorizing in hostile media perception (HMP) has focused on the impact of news content on perceptions of media bias. Using a 2 (an outcome frame versus a value frame) × 2 (a societal frame versus an individual frame) experimental design (N = 114), this study examined the differential effects of news frames on perceptions of media bias. The results showed that an outcome frame induced relatively less HMP than a value frame. Further, a societal frame was more likely to elicit HMP than an individual frame when the medical abortion controversy was framed in term of values (vs. outcomes). Directions for future research on the potential impact of news framing on HMP were discussed.